الحلول الكونية لبعض مشاكل القطع الناقص الغير الخطية بجانب واحد في فضاءات سبوليف متماثل الخواص : Entropy solutions for some nonlinear elliptic unilateral problems in anisotropic Sobolev spaces Dr. Mohammed Al-Houmi (The Scientific Journal of University of Saba Region, 2021)
this paper, we consider the following nonlinear elliptic unilateral equationsof the type In the anisotropic Sobolev space, we prove the existence of entropy solutions forour unilateral problem, the function  is a nonlinear lower order termwith natural growth with respect to , satisfying the sign condition and thedatum f belongs to .